Cryptochrome Interacts With Actin and Enhances Eye-Mediated Light Sensitivity of the Circadian Clock in Drosophila melanogaster - Schlichting, Matthias; Rieger, Dirk; Cusumano, Paola; Grebler, Rudi; Costa, Rodolfo; Mazzotta, Gabriella M.; Helfrich-Förster, Charlotte (Frontiers in Molecular Neuroscience, 2018)
Cryptochromes (CRYs) are a class of flavoproteins that sense blue light. In animals, CRYs are expressed in the eyes and in the clock neurons that control sleep/wake cycles, and are implied in the generation and/or entrainment of circadian rhythmicity. Moreover, CRYs are sensing magnetic fields in insects as well as in humans. Here we show that in the fruit fly Drosophila melanogaster CRY plays a light-independent role as “assembling” protein in the rhabdomeres of the compound eyes. CRY interacts with actin and appears to increase light sensitivity of the eyes by keeping the “signalplex” of the phototransduction cascade close to the membrane. By this way, CRY also enhances light-responses of the circadian clock.